Perception and Digital Media Use of Consumers Who Shop Online - Chuensin, Trichat; Chuchuay, Natthinee; Chanwadee, Kasem (Journal of Modern Learning Development, 2023)
The objectives of this research were to study 1) the accessibility, awareness, and literacy of digital media among consumers who purchased online products, and 2) the digital media usage behavior of consumers who buy online. This is quantitative research. The sample size of the research group was 400 people, randomly selected using the Taro Yamane formula. The error level was 95 percent. The research tools were questionnaires, which collected data by submitting questionnaires via online channels. Data were analyzed using descriptive statistics, including mean, percentage, frequency distribution, and standard deviation. The results of the research revealed that 1) the accessibility, awareness, and digital media literacy of consumers who shop online found that most respondents accessed online shopping via smartphones, followed by tablets, notebooks, and computers, respectively, and they have a high level of digital literacy. 2) The behavior of consumers who shop online when using digital media found that the majority of respondents shop online through TikTok Lives, followed by Facebook Lives, and the least through brand-owned media. By giving reasons to support purchases on such channels, they prefer to watch live sales presentations more. Because they can ask and talk to the seller immediately while the seller goes live selling the product. Most of the respondents cited the reasons for buying products online as being that they were able to make purchases quickly and easily, had the products they wanted to buy available for purchase, and were able to compare quality and prices. Store trust and free shipping are the second reasons.